Environmental Risks 2018
DOI: 10.5772/intechopen.78329
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Riparian Vegetation Changes Downstream of Selected Dams in Vhembe District, Limpopo Province on Based on Historical Aerial Photography

Abstract: Dams have been associated with various impacts on downstream river ecosystems, including a decrease in stream flow, species biodiversity, water quality, altered hydrology and colonisation of the area by invasive alien plant species. The impacts normally interfere with the ecosystem functioning of riparian and aquatic environments, thereby leading to decreased biodiversity. This study aims to assess the impacts of dams on downstream river ecosystems, using data from aerial photographs and orthophotos, supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The river catchment flows showed modest year-to-year changes in response to rainfall trend indicating a low streamflow level that can be attributed to the variations in rainfall. The MNDWI revealed changes in the water surface within the dams of the catchment suggesting a reduction in downstream flow during the drought years [22]. Similarly, the riparian vegetation showed a growth trend in years with high streamflow, while the reverse was the case in other years that experienced severe drought (Figure 6D).…”
Section: Correlation Between Indices and Spi Drought Patterns (1990-2...mentioning
confidence: 89%
See 1 more Smart Citation
“…The river catchment flows showed modest year-to-year changes in response to rainfall trend indicating a low streamflow level that can be attributed to the variations in rainfall. The MNDWI revealed changes in the water surface within the dams of the catchment suggesting a reduction in downstream flow during the drought years [22]. Similarly, the riparian vegetation showed a growth trend in years with high streamflow, while the reverse was the case in other years that experienced severe drought (Figure 6D).…”
Section: Correlation Between Indices and Spi Drought Patterns (1990-2...mentioning
confidence: 89%
“…Buffalo River catchment in the Eastern Cape Province has been experiencing increasing incidences of drought in recent years affecting riparian vegetation health and ecosystem functioning due to the region's aridity and the hydrological complexity of the topographic environment [20,21]. Assessment of riparian vegetation response to water stress in a semi-arid environment especially along river networks is still lacking at the microscale level over a long-term period [22][23][24]. Only a few studies have explored the Buffalo River vegetation change placing limited emphasis on comprehensive riparian vegetation assessment to reveal the topographic complexities along the catchment dynamics because drought conditions are linked to multiple factors [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This area is known for its richness in tropical fruits such as bananas, avocados, mangos, and macadamia nuts amongst others. More water from the dam is used by trees that may result in lowered reservoir water levels (RWLs) as the dam is characterised by a high downstream tree density [29]. Average temperatures in summer are in the 30 • C ranges whilst the winter temperatures vary between 20 • C and 25 • C with a mean annual precipitation of 608 mm.…”
Section: The Study Areamentioning
confidence: 99%
“…A growing body of literature has demonstrated that the construction of dams can also be highly problematic owing to its environmental and socioeconomic impacts [8,[12][13][14][15][16]. A critical question is whether the aims of dam construction and community development can be fulfilled under a single banner.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has had devastating effects on their lives and livelihoods [13]. The construction of dams has also been criticized because it results in the physical transformation of rivers, altering their natural flow [12], ecosystem destruction [4,15,16], and the loss of cultural heritage such as archaeological remains [26]. In addition, dams have been criticized for the lack of benefits accruing to residents and failure in fostering regional development [27].…”
Section: Literature Reviewmentioning
confidence: 99%